Closed tubular mechanical metamaterial as lightweight load-bearing structure and energy absorber. (October 2022) - Chen, Xueyan; Ji, Qingxiang; Iglesias Martínez, Julio Andrés; Tan, Huifeng; Ulliac, Gwenn; Laude, Vincent; Kadic, Muamer
Abstract: Periodic truss-lattice materials, especially when combined with current additive manufacturing techniques, are attracting attention in lightweight material engineering. As a member of the elementary cubic truss family, the simple-cubic truss lattice possesses the highest stiffness and strength along the principal directions and plays an important role in load-bearing mechanical metamaterials. High anisotropic mechanical properties and low resistance to buckling loading and shearing loading, however, limit its use in energy absorption. Here, we present a class of simple-cubic closed tubular lattice with limited loading direction dependence along with high mechanical properties and irregular stable post-yield response. The fabrication of its complex structure was made possible by direct laser writing at the microscale. Experiments and simulations demonstrate that both the elastic modulus and the yield strength of the simple-cubic closed tubular lattice are significantly larger than those of the simple-cubic truss lattice, regardless of the loading direction. At a relative density of 0.1 and compared to the truss lattice, the closed tubular lattice can absorb respectively 4.45 times and 6.14 times as much energy along directions [100] and [110]. The average normalized Young's modulus and yield strength are respectively 28% and 53% larger than those of the most outstanding shellular metamaterial with the same mass. Such excellent mechanical properties make it a potential candidate for applications to load-bearing and energy absorption. Graphical abstract: Highlights: The simple-cubic closed tubular lattice has large and stable mechanical response. Elastic modulus and yield strength outperform the simple-cubic truss lattice. Energy absorption is significantly enhanced along directions [100] and [110]. Energy absorption capacity outperform shellular metamaterials at constant mass.